1998
DOI: 10.1038/sj.jhh.1000612
|View full text |Cite
|
Sign up to set email alerts
|

Plasma renin activity could be a useful predictor of left ventricular hypertrophy in essential hypertensives

Abstract: To clarify the ability of clinical and laboratory parameters to reflect target organ damage, especially left ventricular hypertrophy (LVH), we investigated which of these parameters might correlate to LVH as determined by electrocardiographic voltage at the first clinic visit in 108 (53 males and 55 females, average age 52 ± 10 years) untreated essential hypertensives. The sum of the amplitude of the S wave in lead V 1 plus that of the R wave in lead V 5 or V 6 (SV 1 + R(V 5 , V 6 )) was correlated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
2
0
1
Order By: Relevance
“…These results demonstrate that aliskiren is a highly effective oral renin inhibitor and confirm previous findings that the reactive rise in PRC does not compromise the ability of aliskiren to suppress the activity of renin [12, 13]. The ability of aliskiren to inhibit PRA is likely to be of clinical relevance, as studies have shown that elevated levels of PRA are associated with end organ damage and an increased risk of myocardial infarction in patients with hypertension [6–8], probably due to the increase in Ang II levels associated with increased PRA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results demonstrate that aliskiren is a highly effective oral renin inhibitor and confirm previous findings that the reactive rise in PRC does not compromise the ability of aliskiren to suppress the activity of renin [12, 13]. The ability of aliskiren to inhibit PRA is likely to be of clinical relevance, as studies have shown that elevated levels of PRA are associated with end organ damage and an increased risk of myocardial infarction in patients with hypertension [6–8], probably due to the increase in Ang II levels associated with increased PRA.…”
Section: Discussionsupporting
confidence: 86%
“…However, ACE inhibitors and ARBs only partially suppress the RAAS, because they stimulate a compensatory increase in plasma renin activity (PRA), which may ultimately lead to increased levels of Ang II [5]. Indeed, increased levels of PRA have been associated with end organ damage and poorer clinical outcomes in patients with hypertension [6–8], probably due to the increase in Ang II levels associated with elevated PRA.…”
Section: Introductionmentioning
confidence: 99%
“…There are data that suggest a causal link between circulating renin and the underlying factors leading to HFpEF. High renin levels can increase left ventricular mass (Koga et al, 1998[ 58 ]) either directly or through increases in aldosterone levels (Edelmann et al, 2012[ 27 ]). Renin has also been linked to myocardial fibrosis (Nguyen and Danser, 2008[ 78 ]).…”
Section: Outcomementioning
confidence: 99%
“…Выраженность поражения органов мишеней, в частности ремоделирования левых отделов сердца, почечной дисфункции в зависимости от ренинового профиля изучалась в различных ра-ботах. Множественный регрессионный анализ, предпринятый M. Koga et al (1998) показал, что высокая активность ренина плазмы является предиктором электрокардиографических признаков ГЛЖ как у мужчин, так и у женщин с АГ [31]. данные собственных наблюдений за пациентами с гипертензией, показали, что индексированные по площади поверхности тела масса миокарда левого желудочка и объем левого предсердия, находились в прямой взаимосвязи с концентрацией ангиотензина I и альдостерона в крови [32,33].…”
Section: резюмеunclassified